Development of strength performance monitoring system for lower limb - Mohd Hanif, Razali (2016)
Strength training is a type of physical exercises that practically involves the usage of resistance or load in order to stimulate muscular contraction which builds the strength of the muscles, anaerobic endurance as well as the size of the skeletal muscles. In strength training, weight load is used as for setting up the resistance for the target muscles to act against. This project provides the detailed steps on the design of strength training performance monitoring system for lower limb. Design and fabrication of leg extension machine was made as the exerciser will be the test rig for this study. Inertial measurement unit sensor was used in measuring the displacement of the knee extension as well as the angular velocity and angular acceleration as the training is performed where it was embedded to the movable link of the exerciser. The data recorded in this study were analysed for strength training analysis and compared with literature review of previous research made by others.